DEVELOPING E-MODULE ON IDENTIFICATION OF THE Schistosoma japonicum EGG’S IN HUMAN FECES, NORTH LORE DISTRICT, CENTRAL SULAWESI - uunnadianti; Sutrisnawati Sutrisnawati; Achmad Ramadhan (LPPM Universitas PGRI Semarang, 2024)
The integration of digital technology into education is rapidly expanding. However, the use of technology in learning is often uneven. Limited literature on Schistosomiasis among students contributes to a lack of understanding about this disease. This study aimed to develop a valid, practical, and effective e-module for identifying Schistosoma japonicum worm eggs in human feces in North Lore District, Central Sulawesi. The ADDIE model was employed for the e-module's development, which included stages of needs analysis, design, development, and evaluation. The media and material validity test yielded highly valid results. The e-module's practicality was assessed as highly practical for use in teaching. The effectiveness of the media was determined to be highly effective, with an n-gain test score of 0.76, indicating a high level of learning. Based on these findings, the e-module is deemed valid, practical, and effective for use in biology education. This study is anticipated to be a reference for future researchers developing similar products in other biology subjects.